HUBUNGAN KONFLIK TERHADAP PROFESIONALITAS KERJA GURU UPT SMPN 10 TAPUNG KABUPATEN KAMPAR - Sri Agustina Ratnawati; Ria Rafianti, Refli Surya Barkara, Muhammad Afrillyan Dwi Syahputra (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The purpose of this study is to determine the relationship between work conflict and teacher professionalism in schools, particularly its impact on the quality of individual and organizational performance. Poorly managed work conflicts can disrupt professionalism, such as by reducing commitment, hindering collaboration, or lowering adherence to work standards. Conversely, a high level of professionalism can be a key factor in resolving work conflicts constructively, as professionalism includes the ability to communicate effectively, maintain work ethics, and prioritize shared interests. Therefore, the author is interested in examining the topic "The Relationship Between Conflict and Teacher Professionalism at UPT SMPN 10 Tapung, Kampar Regency." The sample for this study consists of 28 teachers. The results of a simple correlation analysis (r) indicate a correlation between teachers' perceptions of the relationship between conflict and teacher professionalism, with an (r) value of 0.853 and a significance level of 0.05 (5%). This shows a positive relationship, as a higher conflict level correlates with lower teacher professionalism. It can be concluded that the relationship between conflict and teacher professionalism falls into the "very strong" category, with a coefficient range of 0.80–1.00. Thus, it can be stated that interpersonal conflicts are related to teacher professionalism at UPT SMPN 10 Tapung, Kampar Regency